Isolate the m, go backwards for PEMDAS.
C = 2m + d
C (-d) = 2m + d (-d)
C - d = 2m
(C - d)/2 = 2m/2
m = (C - d)/2
m = (C - d)/2 is your answer
hope this helps
Answer:
ASA
Step-by-step explanation:
ASA(Angle-Side-Angle) postulates states that if two angles and one included side of one triangle are congruent to the two angles and one included sides of the other triangle, then these triangles are congruent.
Separate them first.
7+8=15
5/6+2/6=7/6
There can't be 7/6, so it becomes 1 and 1/6,
15+1+1/6=16 1/6
The answer is 16 1/6.
Answer:
proportional/equal
Step-by-step explanation:
doesnt need
Well the formula is : b1+b2/2 (h)
so the height would be solved as :
13.5 = 3+6/2 (h)
13.5 = 9/2 (h)
h = (13.5)/(9/2)
h = (13.5) x (2/9) *reciprocal*
h = (27) / (9)
h = 3